2019
DOI: 10.1101/784967
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic assessment of regulatory effects of human disease variants in pluripotent cells

Abstract: Identifying regulatory genetic effects in pluripotent cells provides important insights into disease variants with potentially transient or developmental origins. Combining existing and newlygenerated data, we established a population-scale resource of 1,367 induced pluripotent stem cell lines derived from 948 unique donors, with matched RNA-sequencing (RNA-seq) and genetic information. The sample size of our study allowed us to significantly expand our knowledge of quantitative trait loci (QTL) in pluripotent… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 76 publications
0
25
0
Order By: Relevance
“…For cell lines that were differentiated multiple times, their differentiation efficiency was taken as the mean of its differentiation efficiencies in the replicate experiments. Gene expression data was available from independent bulk RNA-seq experiments 34 . The feature set was all expressed genes (i.e.…”
Section: Predictive Model Of Differentiation Efficiency From Ipsc Genmentioning
confidence: 99%
See 3 more Smart Citations
“…For cell lines that were differentiated multiple times, their differentiation efficiency was taken as the mean of its differentiation efficiencies in the replicate experiments. Gene expression data was available from independent bulk RNA-seq experiments 34 . The feature set was all expressed genes (i.e.…”
Section: Predictive Model Of Differentiation Efficiency From Ipsc Genmentioning
confidence: 99%
“…To quantify the amount of sharing between each two pairs of eQTL maps (our cell type-condition maps to each of 13 eQTL maps of brain tissues from GTEx) we used the MASHR software 42 . Briefly, the effect sizes (betas) were calculated for each SNP-gene pair across the 14 cell type-condition eQTL maps from our study and extracted from the 13 brain tissues from the GTEx catalogue, as well as two iPSC eQTL maps, using scRNA-seq and bulk RNA-seq respectively 2,34 . Only genes expressed in all GTEx tissues, in iPSC 34 and all of our contexts were included (n=6,205).…”
Section: Sharing Of Eqtl Signal With Gtex Brain Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this gap, we developed a comprehensive map of regulatory variation in the MHC region using deep WGS from 419 individuals and RNA-seq data from matched iPSCs. We have previously shown that iPSCs are well-powered for eQTL mapping (Bonder et al, 2019;Jakubosky et al, 2019a;Jakubosky et al, 2019b), have a distinct regulatory landscape relative to somatic tissues , and thereby provide insights into regulatory variants that exert their effects during early development. While we demonstrate the feasibility of generating a map of regulatory variation for the MHC region and its utility for examining molecular mechanisms underlying disease associations in the interval, future studies using eQTLs from other cell types could increase the number of complex trait loci in the interval that are functionally annotated.…”
Section: Discussionmentioning
confidence: 99%